Los trapiches en Jaris de Mora: Una dulce tradición - López, Claudia L. (2015)
The following papers is the results of several visits made between the months of April and June 2005 in Jaris de Mora village. These is answers to an observation and investigation porcess, which objetive was to analyses the tenseness between the tradition of the "trapiches" in Jaris and the implementation of new techniques in the "dulce" production